Electric Service: The Next Generation - Weil, Gordon (Maine Policy Review, 1995)
In the past few years,Maine’s electric utilities have begun to face the forces of competition.Maineis experiencing the effects of a national trend, a shift from a traditional and regulated system to a more innovative and competitive one. Gordon Weil, active inMaineand elsewhere in promoting increased competition in the electric industry, explains the forces for competition. He traces the history of the electric power market from its beginnings as a monopoly, to its present status where all of the forces promoting competition nationally are at play inMaine.